2011
DOI: 10.1007/s00436-010-2229-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-leishmanial and anti-trypanosomal potential of polygodial isolated from stem barks of Drimys brasiliensis Miers (Winteraceae)

Abstract: Parasitic protozoan diseases affect the poorest population in developing countries. Leishmaniasis and Chagas disease have been included among the most important threats for public health in Central and South American continent, with few therapeutic alternatives and highly toxic drugs. In the course of selection of novel drug candidates, we studied the anti-protozoal potential of Drimys brasiliensis. Thus, the crude hexane extract from stem bark as well as its main derivative, the sesquiterpene polygodial, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 32 publications
1
35
0
1
Order By: Relevance
“…Previous studies have indicated that both a crude hexane extract of D. brasiliensis and polygodial show activity against Leishmania spp when applied in the range of 22-62 µg/mL and polygodial demonstrated high selectivity towards T. cruzi trypomastigotes (2 µg/mL) (Corrêa et al 2011). The drimanes 9-epideoxymuzigadial, 9-deoxymuzigadial, muzigadial and 3-β-acetoxypolygodial isolated from a hexane extract of the leaves of Canella winterana exhibited strong activity against the chloroquine-sensitive strain of P. falciparum, producing IC 50 values of 1.01, 2.19, 0.31 and 2.77 µg/mL, respectively (Grace et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that both a crude hexane extract of D. brasiliensis and polygodial show activity against Leishmania spp when applied in the range of 22-62 µg/mL and polygodial demonstrated high selectivity towards T. cruzi trypomastigotes (2 µg/mL) (Corrêa et al 2011). The drimanes 9-epideoxymuzigadial, 9-deoxymuzigadial, muzigadial and 3-β-acetoxypolygodial isolated from a hexane extract of the leaves of Canella winterana exhibited strong activity against the chloroquine-sensitive strain of P. falciparum, producing IC 50 values of 1.01, 2.19, 0.31 and 2.77 µg/mL, respectively (Grace et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that a hexane extract of the stem bark of Drimys brasiliensis and polygodial, a drimane, exhibit activity against Leishmania spp and Trypanosoma cruzi (Corrêa et al 2011). This information contributes to the further study of this plant species, with the aim of obtaining new drugs to treat the neglected diseases.…”
mentioning
confidence: 99%
“…NCTC (clone 929) cells were maintained in RPMI-1640 (without phenol red and supplemented with 10% FBS) at 37 °C in a humidified atmosphere containing 5% CO 2 [31].…”
Section: Mammalian Cellsmentioning
confidence: 99%
“…In this species, sesquiterpene drimanes are predominant, including polygodial, 1-β-(p-methoxycinnamoyl)-polygodial and drimanial CECHINEL-FILHO et al, 1998;MALHEIROS et al, 2001;. These compounds exhibit antinociceptive (EL-SAYAH et al, 2000), antihyperalgesic (MEN-DES et al, 1998), antifungal (MALHEIROS et al, 2005, anti-inflammatory (LAGO et al, 2010), antibacterial (SILVEIRA et al, 2012), leishmanicidal and antimalarial activities (CORRÊA et al, 2011;CLAUDINO et al, 2013). However, few studies have examined the phytotoxicity of D. brasiliensis on other plants.…”
Section: Introductionmentioning
confidence: 99%